Integrating Gamification and TAM to Drive Purchase Intention in E-Commerce - Satria Fajar Ardianto (Journal of Research on Business and Tourism, 2026)
This paper filled a research gap by integrating gamification and adopting the Technology Acceptance Model (TAM) framework to explore purchase intention among e-commerce users through sales promotion as mediating factors. Gamification, the implementation of game elements in marketing activities, offers an alternative strategy to enhance customer purchase intention. Using a survey method, this study collected 400 valid questionnaires from active e-commerce users in DKI Jakarta who utilize the gamification features. This finding reveal that Perceived Ease of Use and Social Influence positively influence purchase intention. Furthermore, Perceived Usefulness and Perceived Enjoyment positively influence purchase intention through the mediation of Sales Promotion. These findings offer practical guidance for business owners on leveraging gamification to increase purchase intention.